2022
DOI: 10.1039/d2dt00479h
|View full text |Cite
|
Sign up to set email alerts
|

Journey of a molecule from the solid to the gas phase and vice versa: direct estimation of vapor pressure of alkaline-earth metalorganic precursors for atmospheric pressure vapor phase deposition of fluoride films

Abstract: Atmospheric pressure (AP) vapor phase processes such as spatial atomic layer deposition (S-ALD) and AP-metalorganic chemical vapor deposition (AP-MOCVD) are becoming increasingly important for their use in a variety of...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…An MOCVD approach has been successfully applied to the fabrication of BaCeO 3 and Y-doped BaCeO 3 thin films on MgO (100), and yttria-stabilized zirconia (YSZ) (100) substrates, starting from the Ba(hfa) 2 tetraglyme, Ce(hfa) 3 diglyme and Y(hfa) 3 diglyme complexes. The suitability as MOCVD precursors of the above-mentioned adducts, previously synthesized in our group [31][32][33], has been assessed through their application to the fabrication of various materials: (i) the Ce(hfa) 3 diglyme has been applied to the growth of binary CeO 2 thin films [34]; (ii) the Ba(hfa) 2 tetraglyme has been used to fabricate the piezoelectric Ba and Ti co-doped BiFeO 3 textured films [35]; and (iii) the Y(hfa) 3 diglyme has been applied for the fabrication of the YAlO 3 films [36].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…An MOCVD approach has been successfully applied to the fabrication of BaCeO 3 and Y-doped BaCeO 3 thin films on MgO (100), and yttria-stabilized zirconia (YSZ) (100) substrates, starting from the Ba(hfa) 2 tetraglyme, Ce(hfa) 3 diglyme and Y(hfa) 3 diglyme complexes. The suitability as MOCVD precursors of the above-mentioned adducts, previously synthesized in our group [31][32][33], has been assessed through their application to the fabrication of various materials: (i) the Ce(hfa) 3 diglyme has been applied to the growth of binary CeO 2 thin films [34]; (ii) the Ba(hfa) 2 tetraglyme has been used to fabricate the piezoelectric Ba and Ti co-doped BiFeO 3 textured films [35]; and (iii) the Y(hfa) 3 diglyme has been applied for the fabrication of the YAlO 3 films [36].…”
Section: Resultsmentioning
confidence: 99%
“…The synthesis was carried out following the same procedures reported in [31], with the only difference being using dichloromethane instead of toluene. [Ba(OH) 2 •8H 2 O] was first suspended in dichloromethane, and the tetraglyme was added to the suspension.…”
Section: Ba(hfa) 2 Tetraglymementioning
confidence: 99%
“…Plasma technology is an optimal method for surface modification that can be applied quickly and easily with fewer external physical and chemical influences than chemical methods or laser irradiation [19,20]. In this study, material surface modification was carried out through the gas-phase plasma process at atmospheric pressure, which has been used in various fields for a long time, and its safety and effectiveness have been verified [21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that glymes, through oxygen-ion complexation, are very important for the stabilization of alkaline, 61,63,64 alkaline-earth 65,66 and rare-earth 67 metals. The presence of such a class of multidentate ligands, in fact, permits also to fine-tune the properties of the final metal adducts in terms of thermal stability, moisture- and air-sensitivity, solubility, and volatility.…”
Section: Introductionmentioning
confidence: 99%
“…[57][58][59][60][61] Lead β-diketonates are used as precursors in vapor phase processes, such as the case of Pb(tmhd) 2 [(H-tmhd = 2,2,6,6-tetramethyl-3,5-heptanedione)], Pb(acac) 2 , [(H-acac = 2,4-pentanedione)], and their derivatives. 56,62 It has been demonstrated that glymes, through oxygen-ion complexation, are very important for the stabilization of alkaline, 61,63,64 alkaline-earth 65,66 and rare-earth 67 metals. The presence of such a class of multidentate ligands, in fact, permits also to fine-tune the properties of the final metal adducts in terms of thermal stability, moisture-and air-sensitivity, solubility, and volatility.…”
Section: Introductionmentioning
confidence: 99%